Pharmacokinetics of ceftriaxone in patients with typhoid fever. - Acharya, G (1994)
Ceftriaxone in short courses has emerged as an effective alternative to chloramphenicol for the treatment of typhoid fever. To study the pharmacokinetics of ceftriaxone in acute typhoid fever, 10 febrile Nepalese adolescents and young adults with blood culture-positive illness were treated with 3 g of ceftriaxone (intravenous infusion for 30 min) daily for 3 days. On the 1st and 3rd day of treatment, blood and urine samples were collected at defined intervals for measurements of drug concentrations. Kinetic parameters including concentrations at the end of infusion (Cmax) and 24 h after the end of infusion (Cmin), elimination half-life (t1/2), area under the plasma concentration-time curve (AUC), total plasma clearance, renal clearance, percentage excreted in urine, and volume of distribution were estimated. On day 1, mean values were as follows: Cmax, 291 micrograms/ml; Cmin, 21.7 micrograms/ml; plasma t1/2, 5.2 h; AUC, 1,428 micrograms.h/ml; total plasma clearance, 37 ml/min; renal clearance, 19 ml/min; percentage excreted in urine, 49.7%; and volume of distribution, 16.1 liters. Mean values on day 3 were not significantly different from those on day 1. Compared with published values for healthy volunteers who received the same dose, our mean t1/2s and AUCs were lower and our mean total plasma clearances, renal clearances, and volumes of distribution were higher. The good clinical responses of these patients to therapy and the adequate Cmins support the use of ceftriaxone once daily for the treatment of typhoid fever.